Tailoring π-conjugation and vibrational modes to steer on-surface synthesis of pentalene-bridged ladder polymers - de la Torre, Bruno; Matěj, Adam; Sánchez-Grande, Ana; Cirera, Borja; Mallada, Benjamin; Rodríguez-Sánchez, Eider; Santos, José; Mendieta-Moreno, Jesús I; Edalatmanesh, Shayan; Lauwaet, Koen; Otyepka, Michal; Medveď, Miroslav; et al. (Nature communications, 2020)
The development of synthetic strategies to engineer π-conjugated polymers is of paramount importance in modern chemistry and materials science. Here we introduce a synthetic protocol based on the search for specific vibrational modes through an appropriate tailoring of the π-conjugation of the precursors, in order to increase the attempt frequency of a chemical reaction. First, we design a 1D π-conjugated polymer on Au(111), which is based on bisanthene monomers linked by cumulene bridges that tune specific vibrational modes. In a second step, upon further annealing, such vibrational modes steer the twofold cyclization reaction between adjacent bisanthene moieties, which gives rise to a long pentalene-bridged conjugated ladder polymer featuring a low bandgap. In addition, high resolution atomic force microscopy allows us to identify by atomistic insights the resonance form of the polymer, thus confirming the validity of the Glidewell and Lloyd´s rules for aromaticity. This on-surface synthetic strategy may stimulate exploiting previously precluded reactions towards π-conjugated polymers with specific structures and properties.